(untitled) (Research, Society and Development, 2020)
The study of the learning process in the school context is a relevant topic in education since the student has the right to a quality education. The study aims to search for evidence, in the literature, about the learning process from the perspective of the student of youth and adult education – (Educação de Jovens e Adultos – EJA). The motivation of the research was given by the possibility of contributing to the studies that permeate the area of ​​education, mainly in this teaching modality. Some crucial aspects were highlighted, such as learning theories, pedagogical practice and EJA student learning. The methodology used was bibliographic research. The results show the importance of the EJA teacher organizing his didactic action by reviewing his theory of action and seeking support in andragogy, one of the alternatives indicated for working with these students, since it is based on contextual situations that they experience.